Job polarization on local labor markets? - Uwe Blien; Wolfgang Dauth (European Regional Science Association (ERSA), 2016)
In most industrialized countries, employment has grown predominately in jobs at the upper and lower tails of the wage distribution, while employment in the middle part of the distribution has stagnated or declined. This process of job polarization is well documented for a number of countries. We propose a straightforward way to measure the actual magnitude of job polarization and use this measure to compare polarization across German local labor markets. Job polarization almost exclusively occurs in urban areas where the hypothesis of routine biased technological change is most likely to prevail.
Keywords: J31; J24; R23; 330; job polarization; local labor markets; job tasks; routine biased technological change; structural change